2001
DOI: 10.2302/kjm.50.257
|View full text |Cite
|
Sign up to set email alerts
|

Lightning injury as a blast injury of skull, brain, and visceral lesions: clinical and experimental evidences.

Abstract: Abstract. The present study attempts to better understand the mechanism of injuries associated with direct lightning strikes. We reviewed the records of 256 individuals struck by lightning between 1965 and 1999, including 56 people who were killed. Basal skull fracture, intracranial haemorrhage, pulmo nary haemorrhage, or solid organ rupture was suspected in three men who died. Generally these lesions have been attributed to current flow or falling after being struck. However, examination of surface injuries s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…These findings concur with those of Ohashi et al [2][3][4] Despite the difference in size, tearing and tattering occurred in all the papers, suggesting the existence of a non-discriminant blast wave around a long, linear spark (lightning's luminous channel).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings concur with those of Ohashi et al [2][3][4] Despite the difference in size, tearing and tattering occurred in all the papers, suggesting the existence of a non-discriminant blast wave around a long, linear spark (lightning's luminous channel).…”
Section: Resultssupporting
confidence: 91%
“…Ohashi et al [2][3][4] , through a process of elimination, came to the conclusion that blast injury results from the explosive vaporisation of superheated water along the path of the surface flashover. To investigate their hypothesis, an experimental model of a lightning strike was created in the adult Wistar rat.…”
Section: Flash Moisture Vaporisation Theorymentioning
confidence: 99%
“…There are two case reports describing patients with a lightning-related severe blast injury to the lungs, and a third describing an isolated pneumomediastinum presumably secondary to alveolar rupture [5-7]. Postmortem studies of people killed by a lightning strike have shown a significant proportion of blast injuries, and the same authors demonstrated blast injuries to the lungs and other solid organs using artificial lightning in animal models [8]. …”
Section: Discussionmentioning
confidence: 99%
“…97 In an experimental study on rats, similar primary blast injuries to inner organs could be reproduced by the concussive effect of water vaporization due to flash over lightning in wet animals. 64 When lightning strikes, a very large potential difference between the body and the ground is established (Table 1), resulting in a brief, massive current flash over and/or through the body and in induction of secondary electrical currents around the magnetic field pulse of the lightning. The duration of the primary lightning current and the secondary electrical currents is generally too short to cause skin breakdown and lesions by Joule heating, as is characteristic for electrical injuries.…”
Section: Blastmentioning
confidence: 99%